2019
DOI: 10.1155/2019/1021368
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Double Negative Properties in Silver/Silica Random Metamaterials by Precise Control of Microstructures

Abstract: Creative Commons Attribution License (CC BY 4.0).The mechanism of negative permittivity/permeability is still unclear in the random metamaterials, where the precise control of microstructure and electromagnetic properties is also a challenge due to its random characteristic. Here silver was introduced into porous SiO 2 microsphere matrix by a self-assemble and template method to construct the random metamaterials. The distribution of silver was restricted among the interstices of SiO 2 microspheres, which lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The ε-negative property significantly depends on the concentration of free electrons in metacomposites; for example, Shi et al introduced Fe and Ni networks into the porous Al 2 O 3 host and proposed that a high concentration of free electrons can realize excessive ε-negative. , In fact, the ε-negative property greatly relates with the low-frequency plasmonic state of delocalized electrons in metal networks. The high electron density in metals greatly facilitates the formation of plasma oscillation under an alternative electrical field, which generally leads to a high negative value of ε-negative. In addition, the metal-like conduction usually accompanies huge dielectric loss, which hinders the application of the ε-negative property in impedance and permeability matching . The tunable and weakly ε-negative property with a small absolute value of permittivity has been applied in high-permittivity capacitors and perfect absorption. , However, achieving the weakly ε-negative property in metal metacomposites is still difficult and ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…The ε-negative property significantly depends on the concentration of free electrons in metacomposites; for example, Shi et al introduced Fe and Ni networks into the porous Al 2 O 3 host and proposed that a high concentration of free electrons can realize excessive ε-negative. , In fact, the ε-negative property greatly relates with the low-frequency plasmonic state of delocalized electrons in metal networks. The high electron density in metals greatly facilitates the formation of plasma oscillation under an alternative electrical field, which generally leads to a high negative value of ε-negative. In addition, the metal-like conduction usually accompanies huge dielectric loss, which hinders the application of the ε-negative property in impedance and permeability matching . The tunable and weakly ε-negative property with a small absolute value of permittivity has been applied in high-permittivity capacitors and perfect absorption. , However, achieving the weakly ε-negative property in metal metacomposites is still difficult and ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure A, it is observed that with rising frequency ε′ is increased in the frequency range of 1–100 kHz, and after that, the ε′ tends to reach equilibrium with further increasing frequency. The ε′ of BaFe 12 O 19 /PANI nanocomposites with BaFe 12 O 19 loading less than 20 wt % is negative throughout the measured frequency range, which is also observed in the metals’ plasma and reveals that these samples have weak localization of the charge carriers and inherent metallic properties of PANI . Obviously, the absolute value of ε′ in pure PANI is higher than that in 10 and 20 wt % loading of BaFe 12 O 19 /PANI nanocomposites, for the reason that the presence of insulated BaFe 12 O 19 nanoparticles reduces the number of delocalized charge carrier and continuous conductive networks in the PANI matrix .…”
Section: Resultsmentioning
confidence: 68%
“…In addition, it is worth studying the dielectric constant for its own merits as some nanostructured insulators have shown interesting properties such as negative permittivity. 20,21 In this work, we report the liquid-phase exfoliation of BiOCl for the first time. We demonstrate the exfoliation of BiOCl, characterize the resultant nanosheets, and optimize the dispersions for printing.…”
Section: ■ Introductionmentioning
confidence: 93%
“…This is particularly relevant as the exfoliation and printing process can leave residual solvent and polymers in the printed network, which can be difficult, if not impossible, to fully remove. In addition, it is worth studying the dielectric constant for its own merits as some nanostructured insulators have shown interesting properties such as negative permittivity. , …”
Section: Introductionmentioning
confidence: 99%